A Real Time Application of Soft Set in Parameterization Reduction for Decision Making Problem - Janmejay Pant; Amit Juyal; Himanshu Pant; Akhilesh Dwivedi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In each and every field of science and technology Information science plays an important role. Sometimes information science is facing different types of problems to handle the data and information. Data Uncertainty is one of the challenging difficulties to handle. In past, there are several theories like fuzzy set, Rough set, Probability etc.to dealing with uncertainty. Soft set theory is the youngest theory to deal with uncertainty. In this paper we discussed how to find reducts. This paper focuses on how we can transform a sample data set to binary valued information system. We are also going to reduce the dimension of data set by using the binary valued information that results a better decision.